Determinants of Earnings Quality With the Company's Life Cycle, and Related Party Transactions and the Implications on Firm Value - Kurnia, Anita; Apollo Daito (Dinasti Publisher, 2022)
This study aims to prove the empirical effect of the company's life cycle, and related party transactions on earnings quality and its implications toward firm value. This study uses a sample of the mining sector listed on the Indonesia Stock Exchange for the period 2015 – 2020. The sample in this study consisted of 12 companies. Sampling using purposive sampling method and is a quantitative research with panel data regression model.The results show that the company life cycle and related party transactions have a significant positive effect on earnings quality and a significant negative effect on firm value, earnings quality has a significant positive effect on firm value, earnings quality mediates between the firm's life cycle and firm value, and earnings quality does not mediate between related party transactions and firm value.